1940
DOI: 10.1063/1.1712784
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray Method of Determining Rates of Diffusion in the Solid State

Abstract: data to within 0.5 percent in nine cases, and to within 1.0 percent in all cases. While the data are not sufficient to show definitely that the method of calculating densities developed in this paper is applicable to these other types of oils, there seems to be good indication that it is.Two thermodynamic quantities of interest, the isothermal compressibility and the thermal expansivity, can be calculated from the data of this paper. The compressibility can be obtained by differentiation of the density equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(40 citation statements)
references
References 3 publications
0
38
0
2
Order By: Relevance
“…It was Dumond and Youtz [6] who proposed a method of obtaining a very low value of interdiffusivity,/)a, from the decay rate of the first order (n = 1) satellite X-ray intensity, I(t), in multilayered films…”
Section: Interdiffusionmentioning
confidence: 99%
“…It was Dumond and Youtz [6] who proposed a method of obtaining a very low value of interdiffusivity,/)a, from the decay rate of the first order (n = 1) satellite X-ray intensity, I(t), in multilayered films…”
Section: Interdiffusionmentioning
confidence: 99%
“…A review is presented of the formulations [1][2][3][4][5][6][7][8][9][10] for spinodal decomposition that relate to use of the X-ray diffraction method for experimental measurement [21][22][23][24][25][26][27][28][29][30][31][32][33][34] of the time-temperature dependent changes in the composition wave. In particular, reference to formulations and the equations are shown which comprise the basis to compute the higher-order gradient energy coefficients, the diffusion coefficients, and the strain energy variation with nanolaminate spacing.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The macroscopic diffusion coefficient Ď for the alloy system corresponds with an infinite composition wavelength. The relative decay in satellite intensity I ± (t) for the composition fluctuation is normalized to the Bragg peak intensity, and this value is used to determine [22][23][24][25][26]33] the amplification factor R as…”
Section: Modified Diffusion Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when integrated with simple thermal excitation, the kinetics of compositional changes can be directly revealed 7 . For example, as early as 1940, it was shown that XRD methods can be used to study diffusional mixing in solids 8 . These studies, however, have primarily been limited to the quasi-static regime, i.e.…”
mentioning
confidence: 99%